A Study to Assess the Knowledge on Decubitus Ulcer and its Management among the Staff Nurses in Selected Tertiary Care Hospital of Moradabad, Uttar Pradesh: A Original Study (International Journal of Nursing Education, 2019)
Introduction: The prevention and management of pressure ulcer can be a clinical challenge. Decubitus ulcer known as a pressure sore is a wound caused by protracting pressure against the skin. This may occur from disbursing period in one position, causing the weight of the body to compress capillaries against a bed or chair, especially over bony prominences. Aim: The aim of the study was to assess the Knowledge regarding Decubitus Ulcer and its management among the staff Nurses and also to find out the association between the Knowledge regarding Decubitus Ulcer and its management with selected demographic variables. Methodology: Types of studies- Descriptive survey design. Types of Participants- Staff Nurses. Setting- Selected tertiary care hospital of Moradabad. Outcome- Based on the findings and interpretation of the present study, the following conclusion was drawn that 24 (40%) had good level of knowledge and there is a significant association on level of education and working area with level of knowledge